Perlindungan Harta Kekayaan Dalam Pengaturan Perjanjian Perkawinan Di Indonesia - akh Syamsul Muniri; Nur Shofa Ulfiyati (ASASI: Journal of Islamic Family Law, 2021)
The main purpose of marriage is the formation of an eternal, happy, and loving family between husband and wife. However, to anticipate the possibility of problems in marriage, of course a marriage agreement is needed, especially in the distribution of assets. The arrangement of the marriage agreement on the assets of husband and wife is in principle to provide legal protection for husband and wife against their property, if in the future they must divorce. However, the implementation of the marriage agreement as regulated in the Civil Code and Law no. 1 of 1974 concerning Marriage is still limited in time when making a marriage agreement. The legal reforms carried out by the Constitutional Court have given a time limit for the holding of a marriage agreement to be wider so that the factor of wanting to protect each other's property or protect themselves or their families from the threat of domestic violence can be anticipated through a marriage agreement.